Prevention of Hydrosphere Contamination with Electroplating Solutions through Electromembrane Processes of Regeneration - Vasyl Serdiuk (Journal of Ecological Engineering, 2020)
The work studies the process of Сd2+ and Zn2+ cations transfer through a cation-exchange membrane RALEX®CM-PES 11-66 and the cations reduction as metals on the cathodes at the cathode chambers of the electrochemical units with a view to preventing hydrosphere contamination with the electroplating solutions. Electrolysis of the solutions that imitated possible composition of the passivating baths contained 50 g/l sodium dichromate, 10 g/l sulfuric acid and impurity ions of Сd2+ and Zn2+ in various concentrations. The designed passivation solutions with certain amount of impurity ions in the colour solution were forcibly mixed. Impact of the impurity ions concentration in the colour solution and of a forced mixing on the metal reduction was studied. Regularity in increased metal reduction dependent on metal concentration was found and the conditions to favour the ion migration through the cation-exchange membrane due to forced mixing were defined.